EFEITO DA DENSIDADE DE CRIAÇÃO NO DESENVOLVIMENTO ÓSSEO DE FRANGOS DE CORTE ROSS 308 - NOME DOS AUTORES: DA COSTA, Gabriela da Silva; DE SOUZA, Andréia Fróes Galuci Oliveira; SILVA, Higor Jonathan de Oliveira; SILVA, Maria Vitoria; CASSUCI, Leticia Gabriela Talhaferro; MACHADO, Dayane Camargo1 (dayanecamargo1002@gmail.com (ANAIS DO ENIC, 2023)
-